2020
DOI: 10.1101/2020.09.28.315325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The extent of protein hydration dictates the preference for heterogeneous or homogeneous nucleation generating either parallel or antiparallel β-sheet α-synuclein aggregates

Abstract: α-Synuclein amyloid self-assembly is the hallmark of a number of neurodegenerative disorders, including Parkinson’s disease, although there is still very limited understanding about the factors and mechanisms that trigger this process. Primary nucleation has been observed to be initiated in vitro at hydrophobic/hydrophilic interfaces by heterogeneous nucleation generating parallel β-sheet aggregates, although no such interfaces have yet been identified in vivo. In this work, we have discovered that α-synuclein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…19,20 In vitro analysis also showed that α-synuclein can self-assemble at room temperature to produce amyloid-like fibrils under several solution conditions such as low pH, 21 orbital shaking, 22 an air−water interface, etc. 23,24 The protein secondary structure and morphological features of these aggregates are quite similar to those found in the patients' samples. Therefore, the prevention of aggregation of α-synuclein and other such proteins and peptides may be one of the possible treatment options for PD, AD, and other similar amyloid diseases which are becoming a huge burden for society.…”
Section: ■ Introductionsupporting
confidence: 64%
“…19,20 In vitro analysis also showed that α-synuclein can self-assemble at room temperature to produce amyloid-like fibrils under several solution conditions such as low pH, 21 orbital shaking, 22 an air−water interface, etc. 23,24 The protein secondary structure and morphological features of these aggregates are quite similar to those found in the patients' samples. Therefore, the prevention of aggregation of α-synuclein and other such proteins and peptides may be one of the possible treatment options for PD, AD, and other similar amyloid diseases which are becoming a huge burden for society.…”
Section: ■ Introductionsupporting
confidence: 64%
“…3 Alternatively, incubation of αSyn under limited hydration conditions (either PBS with moderate concentrations of alcohols or high concentrations of salts, or upon protein lyophilization in water) promoted αSyn aggregation into structures with an antiparallel intermolecular βsheet structure and particularly slow conversion to fibrils. 28,29 These oligomeric forms, particularly those generated upon αSyn lyophilization and resuspension at high protein concentrations (typically 12 mg•mL −1 ), were morphologically and biologically analogous to the type B oligomers, and were thus named type B* oligomers. 28 Importantly, similar oligomeric species are formed inside neuronal cells, 30 and analogous levels of stress and dysfunction were observed in PD-related cellular models of αSyn aggregation.…”
Section: αSyn Oligomersmentioning
confidence: 99%
“…Recently, Aβ40-WT fibrils with mixed anti-parallel and parallel structures have been observed in the presence of the ganglioside GM1 (41). Moreover, studies on -synuclein have indicated that more hydrophobic environments favor anti-parallel fibril structure over parallel structure (42).…”
Section: Anti-parallel and Parallel Structure In Aβ Fibrils In Sporadic Caamentioning
confidence: 99%